Clinical characteristics and outcomes of influenza-associated pulmonary aspergillosis among critically ill patients: a systematic review and meta-analysis. (February 2022) - Chong, W.H.; Saha, B.K.; Tan, C.K.
Summary: Background: Invasive pulmonary aspergillosis is increasingly identified as a complication of influenza, termed 'influenza-associated pulmonary aspergillosis' (IAPA). Aims: To assess the morbidity and mortality of critically ill influenza patients with and without IAPA. Methods: PubMed, Cochrane Library, Scopus and Embase databases were searched for studies containing comparative data of critically ill influenza patients with IAPA. Primary outcomes were all-cause in-hospital and intensive care unit (ICU) mortality. Secondary outcomes were clinical characteristics; duration of invasive mechanical ventilation (IMV); ICU and hospital length of stay (LOS); and requirement for vasopressor, renal replacement therapy (RRT) and extracorporeal membrane oxygenation (ECMO). Findings: The incidence of IAPA was 28.8% in 853 critically ill influenza patients, with an overall mortality rate of 33.4%. No differences in age and comorbidities were observed. Patients with IAPA were predominantly male and received chronic corticosteroids. In-hospital (49.2% vs 27.0%; P =0.002) and ICU (46.8% vs 20.8%; P <0.001) mortality rates were higher among patients with IAPA than in patients without IAPA. A greater proportion of patients with IAPA required IMV, and had a prolonged IMV duration (mean 17.3 vs 10.5 days; P <0.001), ICU LOS (mean 26.8 vs 12.8 days; P =0.001) and hospital LOS (mean 38.7 vs 27.0 days; P =0.003). Patients with IAPA had greater disease severity and were significantly more likely to require vasopressor (76.4% vs 57.9%; P <0.001), RRT (45.7% vs 19.1%; P <0.001) and ECMO (25.9% vs 12.8%; P =0.004) support compared with patients without IAPA. Conclusions: A diagnosis of IAPA in critically ill patients is associated with greater morbidity and mortality. Early recognition and more research are needed to determine better diagnostic and treatment strategies.